Application of a fibonacci sequence-derived windcatcher scoop louvre geometry for natural ventilation improvement / Babak Rashtian - Rashtian, Babak (2017)
A wind-catcher is a passive strategy to achieve thermal comfort in a building. It helps in the modification of indoor temperature by capturing and channeling outdoor wind flow into the interior space. The rate of fresh air that could be conveyed into a building is a key parameter that determines the performance of a wind-catcher. Fibonacci sequence is a recursive sequence, generated mathematically by adding two previous numbers in the sequence. Its sequence is rhythmic to the natural flow, and as such its application can result in the improvement of effectiveness of aerodynamic dependent products. Examples of contemporary applications are the design of fans, propellers, impellers, and aerators of PAX Scientific Company, established in United States (USA). This study examined how Fibonacci sequence is applied to improve the efficiency of a particular wind-catcher model. It focused on applying Fibonacci sequence principle to formulate the geometry of the louvres of the scoop of a windcatcher system. The study was driven by the same line of inquiry proposed by Jay Harman - "If fluids always tend to follow a particular path, is there a way to design equipment that takes advantage of this fact?" The dissertation began with a presentation on the background and current understanding of wind-catcher and Fibonacci sequencing principles. Computational Fluids Dynamics (CFD) simulation instrument was used to test and analyze the performance of one particular windcatcher model. The performance was measured based on the volumetric airflow where the proposed louvre pattern was compared to a conventional design. The results showed an improvement in the performance of the system by 11%. Further simulation runs were then performed to determine the optimum number of louvres to achieve maximum performance. The results revealed that the wind-catcher with two louvres is optimum. How these values impact the thermal comfort condition of the interior was later investigated using IES software. The results revealed that the increase of wind velocity contribute slightly towards the improvement of the thermal comfort performance of the whole system